2020
DOI: 10.5114/aic.2020.93916
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of anticoagulation following left atrial appendage occlusion with the LARIAT device in patients with nonvalvular atrial fibrillation: impact on thromboembolism, bleeding and mortality. Real life data

Abstract: Introduction: Indications for left atrial appendage occlusion (LAAO) are varied and patients require individual management strategies. However, currently no guidelines exist for postprocedure oral anticoagulation (OAC) after an LAAO procedure.Aim: To evaluate the effect of OAC on thromboembolism, bleeding and mortality following the LAAO procedure for patients with AF.Material and methods: One hundred and thirty-nine consecutive patients with nonvalvular atrial fibrillation (NVAF) who underwent LAAO with the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…We thank Prof. Undas for her interest in our recent article and comments on left atrial appendage occlusion [1]. We agree that our study indirectly points to potential benefits of non-vitamin K oral anticoagulants' (NOAC) use in selected atrial fibrillation (AF) patients following left atrial appendage occlusion (LAAO) in the setting of high thromboembolic and bleeding risk, but a dedicated study is urgently needed to support this concept.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…We thank Prof. Undas for her interest in our recent article and comments on left atrial appendage occlusion [1]. We agree that our study indirectly points to potential benefits of non-vitamin K oral anticoagulants' (NOAC) use in selected atrial fibrillation (AF) patients following left atrial appendage occlusion (LAAO) in the setting of high thromboembolic and bleeding risk, but a dedicated study is urgently needed to support this concept.…”
mentioning
confidence: 78%
“…We presented the real-life observational data on different anticoagulation strategies in atrial fibrillation (AF) patients after LAAO using the LARIAT system between 2009 and 2015 [1]. During this period, the guidelines on oral anticoagulation in AF shifted towards the novel drugs.…”
mentioning
confidence: 99%
“…The Polish recommendations regarding LAA clo sure published in 2018 also presented this uncommonly used surgical technology to occlude the LAA in highrisk AF patients [1]. I read with keen interest the article by Litwinowicz et al in the latest issue of Advances in Intervential Cardiology, in which the authors reported clinical outcomes in 139 patients following the use of the LARIAT device to close the LAA from December 2009 to Decem ber 2010 [2]. A key finding of the study is no difference in rates of thromboembolic and bleeding events as well as mortality between anticoagulated and nonanticoagulat ed AF patients during up to 60 months of followup.…”
mentioning
confidence: 99%
“…A key finding of the study is no difference in rates of thromboembolic and bleeding events as well as mortality between anticoagulated and nonanticoagulat ed AF patients during up to 60 months of followup. The former group involved 75 of the 139 patients, including 40% of anticoagulated subjects on a vitamin K antago nist (VKA) and 18% on nonVKA oral antagonists (NOAC) at the end of followup [2]. Apart from a rather surprising ly large proportion of AF patients in whom the procedure was performed with continued anticoagulation, which had been previously assessed as contraindicated or in effective, it would be interesting to provide data on the indication for LAA closure and quality of anticoagulation with VKA.…”
mentioning
confidence: 99%
See 1 more Smart Citation